2008
DOI: 10.1177/1750481308091910
|View full text |Cite
|
Sign up to set email alerts
|

Emergency communication: the discursive challenges facing emergency clinicians and patients in hospital emergency departments

Abstract: Effective communication and interpersonal skills have long been recognized as fundamental to the delivery of quality health care. However, there is mounting evidence that the pressures of communication in high stress work areas such as hospital emergency departments (EDs) present particular challenges to the delivery of quality care. A recent report on incident management in the Australian health care system (NSW Health, 2005a) cites the main cause of critical incidents (that is, adverse events such as an inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 25 publications
2
29
0
4
Order By: Relevance
“…Communicating in the emergency department will always involve a combination of spoken and written exchanges, with the role of written documentation playing a significant role from both a medicolegal and a clinical perspective (Eisenberg et al 2005;Hobbs 2007;Slade et al 2008). Although our study focused on spoken language in emergency departments, our data indicated that patients' written records were a potential source of miscommunication and risk.…”
Section: Introduce More Effective and Durable Forms Of Patient Recordsmentioning
confidence: 61%
“…Communicating in the emergency department will always involve a combination of spoken and written exchanges, with the role of written documentation playing a significant role from both a medicolegal and a clinical perspective (Eisenberg et al 2005;Hobbs 2007;Slade et al 2008). Although our study focused on spoken language in emergency departments, our data indicated that patients' written records were a potential source of miscommunication and risk.…”
Section: Introduce More Effective and Durable Forms Of Patient Recordsmentioning
confidence: 61%
“…Forståelse kan like mye vaere et spørsmål om erfaring, mening, innlevelse og vilje til deltakelse. Med en rent intellektualistisk tilnaerming er det vanskelig å akseptere at en del deltakere i forskning samtykker uten å ha lest informasjonsskriv (se for eksempel Høyer 2003), eller at pasienter samtykker uten å ha forstått: «Jeg hørte hva legen sa, men jeg forsto ikke hva hun sa» (Slade et al 2008, min oversettelse). Men hvis man legger til grunn at forståelse kanskje i enda større grad dreier seg om erfaringen av tillit eller oppfattelsen av måten man blir møtt på, er slike samtykker på et vis like «gyldige» etisk sett.…”
Section: Det Skjøre Samtykket Og Tillitunclassified
“…One focus in our own healthcare communication research, in both Australia and Hong Kong, has been on communication in emergency (or accident and emergency) departments in large hospitals (for the foundational EDCOM project, see Slade et al 2008;Slade et al 2011). From the point of view of the patient who enters an emergency department, the organizing principle of their visit will be their "journey" through the department, from triage to admission to a hospital ward or, hopefully, discharge.…”
Section: Figure 25mentioning
confidence: 99%